2015
DOI: 10.1063/1.4923437
|View full text |Cite
|
Sign up to set email alerts
|

Stability of spherical converging shock wave

Abstract: Based on Guderley's self-similar solution, stability of spherical converging shock wave is studied. A rigorous linear perturbation theory is developed, in which the growth rate of perturbation is given as a function of the spherical harmonic number ℓ and the specific heats ratio γ. Numerical calculation reveals the existence of a γ-dependent cut-off mode number ℓc, such that all the eigenmode perturbations for ℓ > ℓc are smeared out as the shock wave converges at the center. The analysis is applied to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…37 However, preliminary calculations had shown that the original SLAU2 scheme produced spurious rarefaction waves emitted from the shock front to the center. We found that this effect can be suppressed by increasing the numerical viscosities, especially in the proximity of the shock wave.…”
Section: A Simulations On a Cartesian Gridmentioning
confidence: 99%
See 4 more Smart Citations
“…37 However, preliminary calculations had shown that the original SLAU2 scheme produced spurious rarefaction waves emitted from the shock front to the center. We found that this effect can be suppressed by increasing the numerical viscosities, especially in the proximity of the shock wave.…”
Section: A Simulations On a Cartesian Gridmentioning
confidence: 99%
“…Therefore it is not clear in advance whether or not it becomes unstable for certain values of gas γ and mode number l , just like the converging-shock Guderley solution is. 37 Stability analysis of the reflected-shock Guderley case, will be a natural continuation of both this work and Ref. 37, where such analysis has been done for a converging shock wave.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations